#### You've reached the end of your free preview.

Want to read the whole page?

**Unformatted text preview: **f ( b ) - f (9 )
Find the average rate of change of the function y = -3x3+2x2 -4x +1 between x = 3 and x = 7.
b - a
(958 ) - (-74)
-884
a = 3 f ( b ) = - 3 ( 7 ) ' + 2 ( 7 ) 2 - 4 (7 )+1 - - 958
7 - 3
4
10 = 7 f (a ) = - 3 ( 3) + 2 ( 3)"- 4 (3)+1- -74
8. Use the definition of derivative to find f'(x) for each function.
(a) f(x) = 7x2 - 3x
f' ( x ) = 7.2. X - 3
f' ( x ) $ 14 x - 3
( b ) f ( x ) = 4
f' ( x ) = x
dx
X
4 . * [ * ]. 0 - 4. ax [x ]
X 2
4.1
X 2
- 4
X 2
(c) f (x ) =-6Vx
= [- LJ X ]
-ty - 6 . 2 [ J X] - - 6.4
1/ 2 - 1
3
4 of 5...

View
Full Document

- Fall '19